0
$\begingroup$

Since the dot product has the property that for three vectors $a,b,c$

$a \cdot (b+c) = a \cdot b + a \cdot c$

Is that also true for $(a+b) \cdot (a+b) = a\cdot a + 2a\cdot b + b\cdot b$

?

Thank you

$\endgroup$
1
$\begingroup$

Assuming that you also know the fact that the dot product is commutative, then you can indeed prove the equation you give: \begin{align} (a+b)\cdot(a+b) &= (a+b)\cdot a + (a+b)\cdot b \\ &= a\cdot(a+b) + b\cdot(a+b) \\ &= a\cdot a + a\cdot b + b\cdot a + b\cdot b \\ &= a\cdot a + a\cdot b + a\cdot b + b\cdot b \\ &= a\cdot a + 2a\cdot b + b\cdot b. \end{align}

$\endgroup$
1
$\begingroup$

Yes its true because

$b.a=a.b$ as it is completely scalar.

But distributive property doesnt hold true in case of cross product.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.